Impact of Transcatheter Mitral Valve Repair on Left Ventricular Remodeling in Secondary Mitral Regurgitation: A Meta-Analysis. Issue 6 (2nd November 2018) - Megaly, Michael; Khalil, Charl; Abraham, Bishoy; Saad, Marwan; Tawadros, Mariam; Stanberry, Larissa; Kalra, Ankur; Goldsmith, Steven R.; Bart, Bradley; Bae, Richard; Brilakis, Emmanouil S.; Gössl, Mario; et al.
ABSTRACT: Background: Secondary mitral regurgitation (MR) arises from left ventricular (LV) dilatation and remodeling, and commonly is treated with transcatheter mitral valve repair. We examined the impact of MitraClip on reverse cardiac remodeling in patients with severe, symptomatic secondary MR. Methods: : An electronic search was performed through January 2018 for studies that reported cardiac chamber dimensions prior to and after treatment with MitraClip in patients with secondary MR. The mean difference (MD) with 95% CI was calculated using fixed or random inverse variance models. Outcomes of interest were changes in LV end-systolic and end-diastolic volumes (LVESV, LVEDV) and dimensions (LVESD, LVEDD). Secondary outcomes included left atrial (LA) volume, systolic pulmonary artery pressure (sPAP) and LV ejection fraction (LVEF). Results: A total of 16 studies with 1, 266 patients were included in the present analysis. The weighted mean follow-up period (±SD) was 11.5 ± 7.2 months. MitraClip was associated with significant reduction in LVEDV (−14.24 ml, 95% CI [−22.53, −5.94], p = 0.0008), LVESV (−7.67 ml, CI [−12.30, −3.03], p = 0.001), LVEDD (−2.92 mm [−3.65, −2.19 mm], p < 0.00001), and LVESD (−1.92 mm [−2.92, −0.92], p = 0.0002). MitraClip was also associated with reduction in LA volume (−16.36 ml [23.23, −9.49 ml], p < 0.00001) and sPAP (−6.93 mmHg [−8.76, −5.10], p < 0.00001), and a significant increase in LVEF (+ 2.78% [0.91, 4.66], p = 0.004). Conclusions: In patients with severe symptomatic secondary MR, MitraClip is associated with modest, but favorable LV and LA reverse remodeling. The impact of these changes on clinical outcomes deserves further study.